The Role of Self-Efficacy, Learning Readiness, and Learning Environment on Indonesian Students' Learning Motivation During the Covid-19 Pandemic - Febrianti Febrianti; Kadir Yogurtcu; Nirsuba Gurung (Tinta Emas Publisher, 2025)
This study aims to analyze the role of self-efficacy, learning readiness, and the learning environment on the learning motivation of Indonesian students during the Covid-19 pandemic. The study used a quantitative-explanatory approach with a survey method on active undergraduate students who were taking online lectures at a university in DKI Jakarta. Participants were determined using a purposive sampling technique, with a minimum sample size of 384 students according to the Krejcie table at a 5% error rate. Data were collected using four five-point Likert-scale questionnaires that had been adapted to the Indonesian context and tested for validity and reliability. Data analysis was performed using SPSS through validity tests, reliability tests, classical assumption tests, and multiple linear regression. The results of the analysis showed that self-efficacy, learning readiness, and the learning environment were positively and significantly related to learning motivation, both partially and simultaneously. The coefficient of determination (R²) value of 0.604 indicates that 60.4% of the variation in student learning motivation can be explained by these three variables, while approximately 39.6% is influenced by other factors outside the research model. These findings confirm that strengthening self-efficacy, increasing readiness to learn, and creating a conducive learning environment are important factors in increasing student learning motivation in the context of online learning during and after the pandemic.